Formulation of Skim milk and Soy milk on Producing Soyghurt - Putra, INengah Kencana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2015)
Soyghurt (yoghurt made from soymilk) is better than yoghurt made from cow’s milk because of their lower in cholesterol, saturated fatty acid and lactose content.  Objective of this research was to find out the effect of skim milk and soymilk formulation on the chemical and organoleptik characteristic of soyghurt produced.  This research was designed with a completely randomized design (CRD) with 4 treatments i.e. formulations of skim milk and soy milk 100%:0%, 75%:25%, 50%:50%, and 25%:75%. The results showed formulation of skim milk and soy milk significantly affected the pH, flavor, aroma, and texture, of soyghurt produced, but did not significantly affected the protein content and color. The increase of the level of soy milk tends to lower the pH of soyghurt produced.  Based on the sensory evaluation and chemical analysis the best formulation of skim milk and soy milk in producing soyghurt, was 25% of skim milk and 75% of soymilk. The formulation provided soyghurt with protein content of 4.85%, pH of 4.1, total acid of 0.75%; as well as color preferred, aroma rather preferred, and texture preferred by panelist..
Keywords: soyghurt; soymilk; skim milk; formulation